Effect of short-term exposure to gaseous pollution on asthma hospitalisation in children: a bi-directional case-crossover analysis. Issue 1 (1st January 2003) - Lin, M; Chen, Y; Burnett, R T; Villeneuve, P J; Krewski, D
Abstract : Study objective: Assess associations between short-term exposure to gaseous pollutants and asthma hospitalisation among boys and girls 6 to12 years of age. Design: A bi-directional case-crossover analysis was used. Conditional logistic regression models were fitted to the data for boys and girls separately. Exposures averaged over periods ranging from one to seven days were used to assess the effects of gaseous pollutants on asthma hospitalisation. Estimated relative risks for asthma hospitalisation were calculated for an incremental exposure corresponding to the interquartile range in pollutant levels, adjusted for daily weather conditions and concomitant exposure to particulate matter. Setting: Toronto, Ontario, Canada. Participants: A total of 7319 asthma hospitalisations for children 6 to 12 years of age (4629 for boys and 2690 for girls) in Toronto between 1981 and 1993. Main results: A significant acute effect of carbon monoxide on asthma hospitalisation was found in boys, and sulphur dioxide showed significant effects of prolonged exposure in girls. Nitrogen dioxide was positively associated with asthma admissions in both sexes. The lag time for certain gaseous pollutant effects seemed to be shorter in boys (around two to three days for carbon monoxide and nitrogen dioxide), as compared with girls (about six to seven days for sulphur dioxide and nitrogen dioxide). The effects of gaseous pollutants on asthma hospitalisation remained after adjustment of particulate matter. The data showed no association between ozone and asthma hospitalisation in children. Conclusions: The study showed positive relations between gaseous pollutants (carbon monoxide, sulphur dioxide, and nitrogen dioxide) at comparatively low levels and asthma hospitalisation in children, using bi-directional case-crossover analyses. Though, the effects of certain specific gaseous pollutants were found to vary in boys and girls.